OXYGEN ISOTOPE ANALYSES OF FINE SILICA GRAINS USING LASER-EXTRACTION TECHNIQUE: COMPARISON WITH OXYGEN ISOTOPE DATA OBTAINED FROM ION MICROPROBE ANALYSES AND APPLICATION TO QUARTZITE AND SILCRETE CEMENT INVESTIGATION - Alexandre A.; Basile-Doelsch I.; Sonzogni C.; Sylvestre F.; Parron C.; Meunier J.D.; Colin F. (My University, 2006)
The laser fluorination technique reported here for analyzing the oxygen isotope composition (?18O) of fine quartz size fractions 50-20, 20-10, 10-5, 5-2, 2-1 and <1 ?m has been validated by comparison with the ion microprobe technique. It yields accurate ?18O data with an external precision better than 0.15?. This is a significant methodological improvement for isotopic studies dealing with materials such as soil or biogenic oxides and silicates: particles are often too small and recovered in insufficient amount to be easily handled for ion microprobe analysis. Both techniques were used to investigate ?18O composition of a Cretaceous quartzite and silcrete sequence from the South-East of France. Quartzite cements average 31.04 ? 1.93?. They formed from Mid-Cretaceous seawater. Higher in the series, silcretes cements average 26.66 ? 1.36?. They formed from Upper- or post-Upper-Cretaceous soil water and groundwater. Oxygen isotope data show that the silicification steps from one mineralogical phase to another and from one layer to another (including from an upper pedogenic silcrete to a lower groundwater silcrete) occurred in a closed or weakly evaporating hydrological system. ? 2006 Elsevier Inc. All rights reserved.
Keywords: CHEMICAL ANALYSIS; CRETACEOUS; HYDROGEOLOGY; ION MICROPROBE; ISOTOPIC COMPOSITION; OXYGEN ISOTOPE; Мезозой::Меловая; Mesozoic::Cretaceous